Preservation of Posterior Mitral Leaflet in Mitral Valve Replacement: Effect on Left Ventricular Geometry with Immediate Outcome. (Cardiovascular Journal, 2018)
Bcakground: Preservation of the posterior mitral leaflet and subvalvular structures during mitral valve replacement (MVR) preserve left ventricular geometry and function. We evaluated the effect of preservation of subvalvular structures during mitral valve replacement on LV ejection fraction (LVEF).Methods: Total 60 patients were taken and then grouped into group A and group B. Group A include patients of MVR with preservation of posterior leaflet and subvalvular structure, Group B without preservation of subvalvular structures. All patients were evaluated before operation, at discharge, and at 3 months follow-up. Left ventricular function was assessed by ventricular ejection fraction (LVEF).Results: Preoperative LV ejection fraction was 58.3±11.0% and 56.6±8.4% in Group A and Group B respectively. Post-operative mean LVEF at discharge was found 44.2±5.1% in group A and 37.3±4.8% in group B. Observation at three months follow-up showed that mean LVEF was 49.0±4.7% in group A and 39.6±4.7% in group B.Conclusion: Left ventricular function is better maintained when MVR is done preserving posterior leaflet and subvalvular structure.Cardiovasc. j. 2018; 11(1): 39-41